If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 18p + 3z + -56 = 14 + -1z Reorder the terms: -56 + 18p + 3z = 14 + -1z Solving -56 + 18p + 3z = 14 + -1z Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '56' to each side of the equation. -56 + 18p + 56 + 3z = 14 + 56 + -1z Reorder the terms: -56 + 56 + 18p + 3z = 14 + 56 + -1z Combine like terms: -56 + 56 = 0 0 + 18p + 3z = 14 + 56 + -1z 18p + 3z = 14 + 56 + -1z Combine like terms: 14 + 56 = 70 18p + 3z = 70 + -1z Add '-3z' to each side of the equation. 18p + 3z + -3z = 70 + -1z + -3z Combine like terms: 3z + -3z = 0 18p + 0 = 70 + -1z + -3z 18p = 70 + -1z + -3z Combine like terms: -1z + -3z = -4z 18p = 70 + -4z Divide each side by '18'. p = 3.888888889 + -0.2222222222z Simplifying p = 3.888888889 + -0.2222222222z
| 9.2x-8=2.2x+13 | | -5+5x= | | 9h^2-16=0 | | -(m-4)=-3(m-6) | | (3x+1)=(2x-8) | | C=(b+rm)(l+t) | | (x-2)*(x+5)=400 | | 5(3m+6)=57 | | -5(x+3)=7-(5+x) | | 12x-4=8x-37 | | 8/5x-3=16-2/5x | | P^2-14p+24=0 | | 3(v-2)-6v= | | 4(4-7n)=2(8-n) | | -6x+-5x= | | (46+2x)(65+2x)=4740 | | 3r^2-24r+45=0 | | 12p^2+8p+1=0 | | 3y^3+16y+5=0 | | 4(-b+7)=-(1+7v) | | (x-8)(x+7)=56 | | 17x+-12=114+3 | | 5g^2+44g-9=0 | | 5x+2(5x+8)=8x+18 | | 6p+-3(4p+3)+4(6p+1)=43 | | 5(m-2)=-(6m-1) | | x(x-9)(x+3)=0 | | Z-6.8=7.56 | | 0=6x+x^2-31 | | 1620x-350=680x+470 | | 1/3p-p=12 | | (8x+3)(5x+8)=180 |